Posttraumatic Stress Disorder and Risk of Systemic Lupus Erythematosus Among Medicaid Recipients. Issue 1 (1st September 2022) - Case, Siobhan M.; Feldman, Candace H.; Guan, Hongshu; Stevens, Emma; Kubzansky, Laura D.; Koenen, Karestan C.; Costenbader, Karen H.
Abstract : Objective: We studied posttraumatic stress disorder (PTSD), a severe trauma‐related mental disorder, and systemic lupus erythematosus (SLE) risk in a large, diverse population enrolled in Medicaid, a US government‐sponsored health insurance program for low‐income individuals. Methods: We identified SLE cases and controls among patients ages 18–65 years enrolled in Medicaid for ≥12 months in the 29 most populated US states from 2007 to 2010. SLE and PTSD case statuses were defined based on validated patterns of International Classification of Diseases, Ninth Revision codes. Index date was the date of the first SLE code. Controls had no SLE codes but had another inpatient or outpatient code on the index date and were matched 1:10 to cases by age, sex, and race. Conditional logistic regressions calculated odds ratios (ORs) and 95% confidence intervals (95% CIs) for the association of PTSD with incident SLE, adjusting for smoking, obesity, oral contraceptive use, and other covariates. Results: A total of 10, 942 incident SLE cases were matched to 109, 420 controls. The prevalence of PTSD was higher in SLE cases, at 10.74 cases of PTSD per 1, 000 person‐years (95% CI 9.37–12.31) versus 7.83 cases (95% CI 7.42–8.27) in controls. The multivariable‐adjusted OR for SLE among those with PTSD was 2.00 (95% CI 1.64–2.46). Conclusion: In this large, racially and sociodemographically diverse US population, we found patients with a prior PTSD diagnosis had twice the odds of a subsequent diagnosis of SLE. Studies are necessary to clarify the mechanisms driving the observed association and to inform possible interventions.